A study on investment intention among the young salary-earning class, China - Qi, Peng Cheng; Lim, Thien Sang (Faculty of Business, Economics and Accountancy, UMS, 2022)
Investment participation among young working adults in the Shandong Province of China seems to be lower compared to other major cities such as Beijing and Shanghai. The money market fund, one of the most common investment instruments accessible by most individual investors, is experiencing a decline in recent years. Hence, this study attempt to examine the factors that influence the attitude toward investment, the association between subjective knowledge and self-efficacy, and whether attitude and self-efficacy are associated with investment intention. A research framework based on the Integrated Behavioural Model (IBM) with further support from the Theory of Planned Behaviour was formed. The study follows the Positivism paradigm to examine if the explanatory variables are associated with response variables. The source language questionnaire is English. Hence, all adapted measurement indicators will be translated into the Simple Chinese language for the benefit of the respondents. Seven Hypothesis will be tested using the Smart-PLS. The contribution of this research may benefit the policymakers and financial players (such as Financial Consultants and Investment Firms and Analysts) in helping them to better understand the predictors of investment intention. The study would clarify the complexity of the decision-making process in the field of financial investment. By yielding additional empirical evidence, the study potentially expanding the explanatory power and relevancy of the behavioural financial theory in the mainstream of finance research.